The physics of CT dosimetry : CTDI and beyond - Dixon, Robert L. (Robert Leland), 1940- (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2019)
"This book explores the physics of CT dosimetry and provides practical guidance on best practice for medical researchers and practitioners. A rigorous description of the basic physics of CT dosimetry is presented and illustrates flaws of the current methodology. It will also contain helpful (and rigorous) shortcuts to reduce the measurement workload for medical physicists"--
Introduction and history -- Derivation of dose equations for shift-invariant techniques and the physical interpretation of the CTDI-paradigm -- Experimental validation of a versatile system of CT dosimetry using a conventional small ion chamber -- An improved analytical primary beam model for CT dose simulation -- Cone beam CT dosimetry: a unified and self-consistent approach including all scan modalities -- with or without phantom motion -- Analytical equations for CT dose profiles derived using a scatter kernel of Monte Carlo parentage having broad applicability to CT dosimetry problems -- Dose equations for tube current modulation in CT scanning and the interpretation of the associated CTDIvol -- Dose equations for shift-variant CT acquisition modes using variable pitch, tube current, and aperture, and the meaning of their associated CTDIvol -- Stationary table CT dosimetry and anomalous scanner-reported values of CTDIvol -- Future directions of CT dosimetry and a book summary.
OCLC-licensed vendor bibliographic record.
Keywords: Tomography; Radiation dosimetry; HEALTH & FITNESS / Diseases / General; MEDICAL / Clinical Medicine; MEDICAL / Diseases; MEDICAL / Evidence-Based Medicine; MEDICAL / Internal Medicine; SCIENCE / Physics